Kodifikasi Mushaf Utsmani, Proses Standarisasi dan Distribusi Mushaf - ummu kultsum; Rahmi Damis (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
The study of the process of codification, standardization, and distribution of Ottoman mushaf has a very high historical and scientific value. Through this study, we can understand how the Companions strive to maintain the purity of the revelation of Allah SWT and emulate their prudence in preserving the main source of Islamic teachings. The methodology used in this study is qualitative using descriptive analysis with library research in collecting the data. The result of this research is that the codification of the Qur'an during the time of Caliph Uthman bin 'Affan is a continuation of the efforts to compile the Qur'an which began during the time of Abu Bakr Ash-Siddiq. This codification is carried out due to the increasing expansion of Islamic territory and the emergence of differences in reading (qira'at) among the ummah. Standardization is carried out by establishing a writing system (rasm ottoman) without points and harakat, and maintaining flexibility to accommodate differences in qira'at sahihah. Efforts to codify and standardize during the time of Uthman bin 'Affan became the main milestone in maintaining the authenticity of the Qur'anic text. .